IMPLEMENTATION OF AL-GHAZALI’S ISLAMIC EDUCATION PHILOSOPHY IN THE MODERN ERA - Muflihin, Ahmad; Madrah, Muna Yastuti (Universitas Islam Sultan Agung, 2019)
ABSTRACTPhilosophy and education are two things that cannot be separated. Philosophy is the basic foundation or direction for achieving the implementation and goals of education. Education aims to shape human beings in achieving complete humanity. Even Islam offers a concept of human beings, namely the prototype of humans who carry out their duties as khalifatullah fil ardh; humans who not only have intellectual intelligence (IQ), but also spiritual (SQ) and emotional intelligence (EQ). The problems that arise, complaints about the increasingly widespread individualist, materialist, and pragmatic nature of the community are allegedly because the modern education system ignores the basics of the value of education and only pursues material benefits. This article offers a solution to answer the challenges of education in the modern era which refers to the philosophical value of education. Especially the concept of the philosophy of Islamic education taught by al-Ghazali. In his education philosophy, al-Ghazali did not recognize the separation between religious education and general education without linking of them. There is no aqliyah term without including syar'iyyah. Cognitive aspects are not developed without involving affective and psychomotor aspects at once. Because faith, knowledge, and charity always go side by side.Â Keywords: Philosophy, al-Ghazali, Education, Modern Era, Islamic Education